The forgotten - Wiesel, Elie, 1928-2016 (Schocken Books : Distributed by Pantheon Books, 1995)
A profoundly moving novel about a Holocaust survivor's struggle to remember both the heroic and the shameful events of his past, and about his American-born son's need to assimilate his father's life into his own.